176例再生障碍性贫血患者门诊治疗真实世界研究 (Zhonghua Xue Ye Xue Za Zhi, 2021)
OBJECTIVE: To explore the diagnostic process and outcomes of patients with aplastic anemia (AA) who received outpatient treatment in a real-world setting. METHODS: The diagnostic processes, treatment regimens, and outcomes of 176 patients with AA treated in outpatient centers from January 2018 to December 2019 were reviewed. RESULTS: The median interval from the onset of symptoms to the first visit was 7 (5–120) months. Complaints during the first visit included bleeding (52.3%), anemia (51.7%), and infection (6.8%). For diagnosis, 168 patients (95.5%) underwent bone marrow aspiration; however, only 22 of them (17.1%) consented aspiration in multiple sites (sternum). The completion rate of bone marrow biopsy was 85.1% (143/168) ; flow immunophenotype and karyotype analyses were performed on 59.5% (100/168) and 58.9% (99/168) of AA patients, respectively, and the culture of clonal forming units by bone marrow mononuclear cells was performed on 26.8% (45/168) of AA patients. The most preferred regimen was cyclosporine combined with androgen and levamisole (43.8%, 77 patients), followed by cyclosporine combined with androgen (25.6%, 45 patients). Cyclosporine alone was administered in 24 patients (13.6%) and androgen alone in 16 patients (9.1%). Furthermore, 14 patients (7.9%) did not consent to any drugs or only chose traditional Chinese medicine. The patients were divided according to the frequencies of follow-up: regular follow-up group (≥4 times/year, n=130) and irregular group (<4 times/year, n=46). The former had a higher 6-month remission rate (52.5% vs 28.0%, P=0.005), a greater high-quality remission rate in 12 months (40.7% vs 16.7%, P=0.027), and a lower relapse rate in 24 months (4.4% vs 36.4%, P=0.001). CONCLUSION: In real-world settings, bone marrow aspiration in multiple sites should be addressed in outpatient treatment for AA diagnostic work-up, including PNH clone screening, flow immunophenotype, chromosome karyotype analysis, and culture of clonal forming units. Patients with AA who follow regular visits were more likely to achieve high-quality remission and a lower relapse rate. Visits at least four times per year are recommended for AA patients undergoing outpatient treatment.